Enhanced Biosynthesis of Fatty Acids Contributes to Ciprofloxacin Resistance in Pseudomonas aeruginosa - Su, Yu-bin; Tang, Xi-kang; Zhu, Ling-ping; Yang, Ke-xin; Pan, Li; Li, Hui; Chen, Zhuang-gui (Frontiers in Microbiology, 2022)
Antibiotic-resistant Pseudomonas aeruginosa is insensitive to antibiotics and difficult to deal with. An understanding for the resistance mechanisms is required for control of the pathogen. Here, GC-MS based metabolomics was performed to identify differential metabolomes in ciprofloxacin-resistant P. aeruginosa strains that originated from ATCC 27853 and had MICs that were 16-, 64- and 128-fold (PA-R16CIP, PA-R64CIP and PA-R128CIP, respectively) higher than the original value, compared to ciprofloxacin-sensitive P. aeruginosa (PA-S). Upregulation of fatty acid biosynthesis forms a characteristic feature of the ciprofloxacin-resistant metabolomes and fatty acid metabolome, which was supported by elevated gene expression and enzymatic activity in the metabolic pathway. The fatty acid synthase inhibitor triclosan potentiates ciprofloxacin to kill PA-R128CIP and clinically multidrug-resistant P. aeruginosa strains. The potentiated killing was companied with reduced gene expression and enzymatic activity and the returned abundance of fatty acids in the metabolic pathway. Consistently, membrane permeability was reduced in the PA-R and clinically multidrug-resistant P. aeruginosa strains, which was reverted by triclosan. Triclosan also stimulated uptake of ciprofloxacin. These findings highlight the importance for the elevated biosynthesis of fatty acids in ciprofloxacin resistance of P. aeruginosa and provide a target pathway for combating ciprofloxacin-resistance P. aeruginosa.